2022
DOI: 10.3390/plants11030351
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chitosan-24-Epibrassinolide Composite Coating on the Quality Attributes of Late-Harvested Pomegranate Fruit under Simulated Commercial Storage Conditions

Abstract: This study evaluated the efficacy of chitosan (CH) functionalized with 24-epibrassinolide (EBR) coating in terms of preserving the postharvest quality of late-harvested pomegranate (cv. Wonderful) fruit. Late-harvested pomegranate fruit were immersed for 3 min in different surface treatment solutions—CH 1.5% (w/v), CH + 2 µM EBR, CH + 5 µM EBR, CH + 10 µM EBR and CH + 15 µM EBR—and distilled water was used as a control treatment. The fruit were air-dried and subjected to long storage duration at 5 °C with 85 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 64 publications
(113 reference statements)
8
6
0
Order By: Relevance
“…This finding supports the results of a previous study of kiwi fruit where EBR was shown to be effective in decreasing weight loss during storage 23 . Our results are also consistent with those obtained in pomegranates, showing that an EBR + CT coating contributed to reducing weight loss 24 . Edible coats form a semipermeable layer that reduces water evaporation 25 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding supports the results of a previous study of kiwi fruit where EBR was shown to be effective in decreasing weight loss during storage 23 . Our results are also consistent with those obtained in pomegranates, showing that an EBR + CT coating contributed to reducing weight loss 24 . Edible coats form a semipermeable layer that reduces water evaporation 25 .…”
Section: Discussionsupporting
confidence: 92%
“…2(d)–(f)). These results are in line with those reported in similar studies of pomegranates 24 . Numerous authors also highlighted the efficacy of EBR in maintaining the quality of different crops, such as kiwis 4,23 and table grapes, 29 and delaying their ripening during storage.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Ruby) with prolonged storage at different storage conditions for 12 weeks. Similarly, Mwelase and Fawole (2022) reported a significant decrease in TSS contents of ‘Wonderful’ pomegranates treated with chitosan combined with epibrassinolide during storage for 12 weeks at 5°C. However, Ghafir et al (2010) reported an increase in TSS of “Shlefy” pomegranate fruit during 16 weeks of storage at 5 and 7°C, respectively.…”
Section: Resultsmentioning
confidence: 81%
“…AgNPs induce the activity of PAL enzymes and showed increase initially [80] and then slight decline in phenolic content of treated banana as compared to control. Another enzyme PPO oxidized the phenolic content in untreated banana by using oxygen as co-substrate and the lower concentration of oxygen could be the reason to reduce phenolic content [70,73,81] while the AgNPs application on fruits enable them to maintain the phenolic content throughout the storage [38].…”
Section: Plos Onementioning
confidence: 99%